2018
DOI: 10.1111/1754-9485.12738
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of dual‐phase cone‐beam computed tomography during arteriography and automated tumour‐feeder detection software in transarterial embolization for obscure arterial bleeding in the abdomen

Abstract: We report the usefulness of dual-phase cone-beam computed tomography during angiography (CBCTA) and automated tumour-feeder detection software (AFD) in transarterial embolization (TAE) for three consecutive cases of obscure arterial bleeding in the abdomen. Two patients presented with lower gastrointestinal bleeding and one showed bleeding into the pancreatic pseudocyst. Superior mesenteric or common hepatic angiography did not demonstrate extravasation, but dual-phase CBCTA and AFD could identify extravasatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…CBCT has been known for its role in confirming segmental distribution of hepatocellular carcinoma during chemoembolization. However, CBCT has also provided more utility in identifying GI bleeds difficult to localize with digital subtraction angiography alone [11]. A greater interval between dual phases during CBCT and higher concentrated contrast material may increase the likelihood of detecting extravasation in an active bleed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBCT has been known for its role in confirming segmental distribution of hepatocellular carcinoma during chemoembolization. However, CBCT has also provided more utility in identifying GI bleeds difficult to localize with digital subtraction angiography alone [11]. A greater interval between dual phases during CBCT and higher concentrated contrast material may increase the likelihood of detecting extravasation in an active bleed.…”
Section: Discussionmentioning
confidence: 99%
“…A greater interval between dual phases during CBCT and higher concentrated contrast material may increase the likelihood of detecting extravasation in an active bleed. While Carrafiello et al utilized a 15-second interval between the first and second phase of CBCT and 300 mg I/mL contrast material, Miyayama et al utilized a 30-second interval and 370 mg I/mL contrast concentration [11,12]. While Carrafiello et al found the active bleed in 19/20 of their patients using dual phase CBCT, Miyayama et al found the bleed in all three of their obscure GI bleed patients [11,12].…”
Section: Discussionmentioning
confidence: 99%